Sloshing Simulation of Three Types Tank Ship on Pitching and Heaving Motion - Edi Jadmiko; Yoga Adhi Pratama (Institut Teknologi Sepuluh Nopember, 2017)
As an important part of a ship, tanker / cargo hold specifically designed to distribute the load to be maintained safely. In a related IMO classification of LNG carrier, there are a wide variety of types of LNG tanks on ships. Are generally divided into two types, namely tank (Independent Self Supporting Tank) and (Non Self Supporting Tanks). The tank-type variation will affect the characteristics of fluid motion that is inside the tank. Need for simulation of sloshing and analysis of the structure of the tank due to the force created by the load when the heaving and pitching. Sloshing the effect of the free movement of the fluid in the tank with the striking motion wall tank walls that can damage the walls of the tank. Type 1 tank is a tank octagonal (octogonal) for membrane-type LNG carrier with dimensions of length 38 m width 39.17 m 14.5 m high side of the tank. Type 2 tank is a tank-shaped capsule with the long dimension of 26.6 m and a diameter of 10.5 m. Type 3 tank is rectangular tank (rectanguler) with dimensions of length of 49.68 m, width 46.92 and 32.23 m high. Simulations conducted using Computational Fluid Dynamic (CFD) using ANSYS FLUENT software. From the simulation results concluded that the tank 1 to form (octogonal) have a total pressure of 3013.99 Pa on the front wall with a height of 13.65 m from the base of the tank